Authoritarian origins of democratic party systems in Africa - Riedl, Rachel Beatty (Cambridge ; New York : Cambridge University Press, 2014)
"Faced with a transition to multiparty democracy, many assume that b reaking the power of incumbents is necessary to develop a stable, highl y institutionalized party system. But, in fact, across Sub-Saharan Afri ca, the incumbent's demise is sufficient to ensure a highly volatile, w eakly institutionalized party system in the democratic era. A strong au thoritarian incumbent produces a more coherent, stable party competitio n, with the unintended consequences of promoting national territorial c overage; stronger partisan identities; opposition cohesion; and, ultima tely, democratic accountability. In Ghana, for example, the incumbent m ilitary leader and authoritarian revolutionary J. J. Rawlings and his N ational Democratic Congress (NDC) party swept the founding elections in 1992. Since that time, Ghana has developed a highly institutionalized party system with low levels of volatility and an alternating majority between stable parties. Ghana has experienced two democratic turnovers, and the two major parties, the NDC and the New Patriotic Party (NPP), are deeply connected to their constituencies, they organize across the national territory to compete in every constituency, they mobilize part icipation during and beyond elections, and they aggregate coalitions of diverse citizens and interests. The NDC and the NPP alike are enduring entities that help shape individual partisan identities and structure national, regional, and local competition"--
Includes bibliographical references (pages 233-252) and index.
Keywords: Political parties -- Africa, Sub-Saharan.; Democratization -- Africa, Sub-Saharan.; Democracy -- Africa, Sub-Saharan.; Political parties -- Ghana; Democratization -- Ghana; Democracy -- Ghana; POLITICAL SCIENCE / General; Africa, Sub-Saharan -- Politics and government; Ghana -- Politics and government -- 2001-